The Power Grid Inertia With High Renewable Energy Sources Integration: A Comprehensive Review - Abderrahmane Smahi; Salim Makhloufi (Journal of Engineering)
The accelerating integration of renewable energy sources (RESs) into power grids poses a significant challenge to system inertia, primarily due to a reduced dependence on conventional synchronous generators (SGs). This transition profoundly affects frequency stability, rendering grids more susceptible to disturbances. This review offers an in-depth examination of contemporary and emerging strategies to bolster grid inertia, with a focus on virtual synchronous machines (VSMs), advanced energy storage systems, and the transformative potential of artificial intelligence (AI) in optimizing inertia emulation. Unlike prior reviews that primarily catalog existing approaches, this work distinguishes itself by presenting a comparative analysis of various VSM topologies tailored to distinct RES integration contexts, supplemented by real-world case studies and a comprehensive SWOT analysis of AI-driven inertia solutions. The results provide practical insights and guidance for both researchers and industry professionals, underscoring the importance of these adaptive strategies in fostering resilient, sustainable power systems essential for the energy transition.